2015
DOI: 10.1039/c5cy00073d
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and DFT studies on Sr-doped LaMnO3 catalysts for NOx storage and reduction

Abstract: The idea of rational design of perovskite catalysts for NO x storage and reduction (NSR) starts from DFT studies on Sr-doped LaMnO 3 (001) plane models: a Mn-terminated plane (Mn-ter) has a higher activity than La-or Sr-ter planes; the number of A-site defects increases when Sr is doped on the surface; O-vacancy formation energies for both La-and Mn-ter gradually decrease with increased Sr loading, and the values for La-ter are always larger than for Mn-ter with the same Sr loading, indicating that the O-vacan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 40 publications
1
32
0
Order By: Relevance
“…Perovskite materials mostly applied for removing common exhaust pollutants including carbon monoxide, hydrocarbon, ammonia oxidation, water dissociation, and NOx, etc. 13 . Amongst different perovskite, Mn-containing oxide materials have been growing a considerable interest from the researchers because of the large specific external area, high thermo-chemical durability and extraordinary catalytic performance even at environmental conditions 29 .…”
Section: Introductionmentioning
confidence: 99%
“…Perovskite materials mostly applied for removing common exhaust pollutants including carbon monoxide, hydrocarbon, ammonia oxidation, water dissociation, and NOx, etc. 13 . Amongst different perovskite, Mn-containing oxide materials have been growing a considerable interest from the researchers because of the large specific external area, high thermo-chemical durability and extraordinary catalytic performance even at environmental conditions 29 .…”
Section: Introductionmentioning
confidence: 99%
“…Obviously, according to the characterizations in this research, the greater exposure of B-site transition-metal cations on the surface is the main factor for the ORR catalytic activity. It has been also noted that the surface with Mn has higher activity than those with La or Sr via the calculation with density functional theory [59]. In addition, the increased specific surface area and the mesoporous structure improve the ORR activity by providing more active sites and mass-transfer channels.…”
Section: Resultsmentioning
confidence: 99%
“…Some of the studies reported in Table 1 have been focused on understanding the electronic structure of perovskites [54,69,71]. Specifically, Density Functional Theory (DFT) calculations have been carried out to analyze the NO-to-NO 2 reaction on LaCoO 3 -type perovskites.…”
Section: Nox Adsorption Under Oxidizing Conditionsmentioning
confidence: 99%